Coevolution of Metabolic Pathways in Blattodea and Their Blattabacterium Endosymbionts, and Comparisons with Other Insect-Bacteria Symbioses - Kinjo, Yukihiro; Bourguignon, Thomas; Hongoh, Yuichi; Lo, Nathan; Tokuda, Gaku; Ohkuma, Moriya (Microbiology spectrum, 2022)
Many insects harbor bacterial endosymbionts that supply essential nutrients and enable their hosts to thrive on a nutritionally unbalanced diet. Comparisons of the genomes of endosymbionts and their insect hosts have revealed multiple cases of mutually-dependent metabolic pathways that require enzymes encoded in 2 genomes. Complementation of metabolic reactions at the pathway level has been described for hosts feeding on unbalanced diets, such as plant sap. However, the level of collaboration between symbionts and hosts that feed on more variable diets is largely unknown. In this study, we investigated amino acid and vitamin/cofactor biosynthetic pathways in Blattodea, which comprises cockroaches and termites, and their obligate endosymbiont Blattabacterium cuenoti (hereafter Blattabacterium). In contrast to other obligate symbiotic systems, we found no clear evidence of "collaborative pathways" for amino acid biosynthesis in the genomes of these taxa, with the exception of collaborative arginine biosynthesis in 2 taxa, Cryptocercus punctulatus and Mastotermes darwiniensis. Nevertheless, we found that several gaps specific to Blattabacterium in the folate biosynthetic pathway are likely to be complemented by their host. Comparisons with other insects revealed that, with the exception of the arginine biosynthetic pathway, collaborative pathways for essential amino acids are only observed in phloem-sap feeders. These results suggest that the host diet is an important driving factor of metabolic pathway evolution in obligate symbiotic systems. IMPORTANCE The long-term coevolution between insects and their obligate endosymbionts is accompanied by increasing levels of genome integration, sometimes to the point that metabolic pathways require enzymes encoded in two genomes, which we refer to as "collaborative pathways". To date, collaborative pathways have only been reported from sap-feeding insects. Here, we examined metabolic interactions between cockroaches, a group of detritivorous insects, and their obligate endosymbiont, Blattabacterium, and only found evidence of collaborative pathways for arginine biosynthesis. The rarity of collaborative pathways in cockroaches and Blattabacterium contrasts with their prevalence in insect hosts feeding on phloem-sap. Our results suggest that host diet is a factor affecting metabolic integration in obligate symbiotic systems.
Keywords: symbióza; kyselina listová; aminokyseliny; švábi; Insecta; Vitamins; esenciální aminokyseliny; fylogeneze; Phylogeny; Genome, Bacterial; Bacteria; co-evolution; Folic Acid; Arginine; Amino Acids, Essential; genom bakteriální; vitaminy; Animals; hmyz; insects; zvířata; Cockroaches; metabolické sítě a dráhy; endosymbiosis; arginin; Symbiosis; Blattabacterium; Metabolic Networks and Pathways; Amino Acids; co-metabolism; Blattodea